KEPATUHAN HUKUM REPUBLIK DEMOKRATIK KONGO TERHADAP CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA (CITES) ATAS PERLINDUNGAN POHON TROPIS AFRORMOSIA - Masyitha Salsabila (BELLI AC PACIS (Jurnal Hukum Internasional), 2021)
Trees are forest products whose number continues to decrease over time due to fulfilling human needs to sustain their lives. Continuous deforestation can threaten and destabilize ecosystems on earth, which leads to international environmental issues that have yet to be resolved. The purpose of this legal research was to determine the legal compliance of the Democratic Republic of the Congo (DRC) towards regulations by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) for the protection of the tropical Afromosia tree and the steps that the DRC should undertake in maintaining the existence of the Afromosia tree which is now endangered from extinction. This study is normative legal research with a statute and case approach and analyzed through inductive analysis techniques. Make use of indicators from the international legal compliance theory by Andrew T. Guzman, namely the model of rational and self-interested states theory, the results of the study show that the DRC has a low level of legal compliance with the provisions of the CITES convention related to the protection of Afrormosia trees.